Oligonucleotide Enhancing Compound Increases Tricyclo-DNA Mediated Exon-Skipping Efficacy in the Mdx Mouse Model - Flavien Bizot; Abdallah Fayssoil; Cécile Gastaldi; Tabitha Irawan; Xaysongkhame Phongsavanh; Arnaud Mansart; Thomas Tensorer; Elise Brisebard; Luis Garcia; Rudolph L Juliano; Aurélie Goyenvalle (Cells, 2023)
Nucleic acid-based therapeutics hold great promise for the treatment of numerous diseases, including neuromuscular disorders, such as Duchenne muscular dystrophy (DMD). Some antisense oligonucleotide (ASO) drugs have already been approved by the US FDA for DMD, but the potential of this therapy is still limited by several challenges, including the poor distribution of ASOs to target tissues, but also the entrapment of ASO in the endosomal compartment. Endosomal escape is a well recognized limitation that prevents ASO from reaching their target pre-mRNA in the nucleus. Small molecules named oligonucleotide-enhancing compounds (OEC) have been shown to release ASO from endosomal entrapment, thus increasing ASO nuclear concentration and ultimately correcting more pre-mRNA targets. In this study, we evaluated the impact of a therapy combining ASO and OEC on dystrophin restoration in mdx mice. Analysis of exon-skipping levels at different time points after the co-treatment revealed improved efficacy, particularly at early time points, reaching up to 4.4-fold increase at 72 h post treatment in the heart compared to treatment with ASO alone. Significantly higher levels of dystrophin restoration were detected two weeks after the end of the combined therapy, reaching up to 2.7-fold increase in the heart compared to mice treated with ASO alone. Moreover, we demonstrated a normalization of cardiac function in mdx mice after a 12-week-long treatment with the combined ASO + OEC therapy. Altogether, these findings indicate that compounds facilitating endosomal escape can significantly improve the therapeutic potential of exon-skipping approaches offering promising perspectives for the treatment of DMD.